Determinan Audit Report Lag Dengan Auditor Spesialisasi Industri Sebagai Variabel Moderating Pada Perusahaan Go Public Sektor Pertambangan Terdaftar Di Bei Periode 2014-2018 - Harahap, Aulia Rahman; Irfan, Irfan; Mayasari, Mayasari; Siregar, Nancy Mayriski (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The purpose of the study was to examine the effect of audit committee size, auditor tenure and KAP size on audit report lag with industry specialization auditors as moderating variables in publicly listed mining sector companies on the IDX. This research is a quantitative research using secondary data that is accessed from the website of the mining sector company. This study uses the criteria to determine the research sample, amounting to 31 companies. The method of analysis used logistic regression and residual test which was processed with SPSS. The results of the study: 1) the size of the audit committee has no effect on audit report lag; 2) audit tenure has no effect on audit report lag; 3) KAP size has an effect on audit report lag; 4) all independent variables simultaneously affect the audit report lag; 5) the moderating variable cannot moderate the effect of the independent variable on audit report lag.